The Rac inhibitor HV-107 as a potential therapeutic for metastatic breast cancer - Grace Velez Crespo; Jescelica Ortiz; Eliud Hernández O'Farrill; Cornelis P. Vlaar; Mikhail Inyushin; Yuriy Kucheryavykh; Lilia Kucheryavykh (BMC, 2023)
Abstract Background The significant challenge in treating triple-negative breast cancer (TNBC) lies in its high rate of distant metastasis. To address this, inhibiting metastasis formation in TNBC is vital. Rac is a key player in cancer metastasis. Previously, we developed Ehop-016, a Rac inhibitor that successfully reduced tumor growth and metastasis in mice. In this study, we assessed the effectiveness of HV-107, a derivative of Ehop-016, in inhibiting TNBC metastasis at lower doses. Methods Rho GTPases activity assays were performed with the use of GST-PAK beads and Rac, Rho, and Cdc42 GLISA. Cell viability was assessed through trypan blue exclusion and MTT assays. Cell cycle analysis was conducted using flow cytometry. To evaluate invading capabilities, transwell assays and invadopodia formation assays were performed. Metastasis formation studies were conducted using a breast cancer xenograft mouse model. Results HV-107 inhibited Rac activity by 50% in MDA-MB-231 and MDA-MB-468 cells at concentrations of 250-2000 nM, leading to a 90% decrease in invasion and invadopodia activity. Concentrations of 500 nM and above caused dose-dependent reductions in cell viability, resulting in up to 20% cell death after 72 h. Concentrations exceeding 1000 nM upregulated PAK1, PAK2, FAK, Pyk2, Cdc42, and Rho signallings, while Pyk2 was downregulated at 100-500 nM. Through in vitro experiments, optimal concentrations of HV-107 ranging from 250 to 500 nM were identified, effectively inhibiting Rac activity and invasion while minimizing off-target effects. In a breast cancer xenograft model, administration of 5 mg/kg HV-107 (administered intraperitoneally, 5 days a week) reduced Rac activity by 20% in tumors and decreased metastasis by 50% in the lungs and liver. No observed toxicity was noted at the tested doses. Conclusion The findings indicate that HV-107 exhibits promising potential as a therapeutic medication utilizing Rac inhibition mechanisms to address metastasis formation in TNBC.